Fostering Grassroots Economy of the Local Community: A Lesson Learned Study - Naphat Soicjit; Akkarajet Chaiyaphum; Tawatchai Kahaban; Yuttapong Khuenkhaew; Suchanart Singhapat; Naruechit Saenpakdee; Nittaya Kahaban (Journal of Educational Issues, 2024)
The purposes of this research are to 1) analyze the lessons learned by communities in the process of developing their basic economies, and 2) present a collaborative learning and development approach for building the underlying economy of the community. The research is qualitative and based on cultural anthropological research standards. The population used in this study consisted of 15 members of a community enterprise group in Nongpaen Sub-district, Kamalasai District, and Kalasin Province. A purposive sample of 185 people was selected. Research tools include interviews and group discussions, descriptive data analysis, and analysis. Collect data from a collection of relevant documents and ideas to present guidelines for the development of the University to Tambon (U2T) project’s grassroots economy. The results showed that: 1) community learning for essential economic growth starts with figuring out how to deal with problems; community leaders will work together to combine lessons and come up with joint solutions, and 2) community learning initiatives increase the foundation economy’s capacity for productive community enterprise growth. Three variables were discovered to have an impact on the operation: production variables, quality variables, and marketing variables. The public or private sectors must build and support the foundation economy to be stable and sustainable and promote product knowledge. The neighborhood can become independent in terms of marketing and product quality.